Muddy ground Native peoples, Chicago's portage, and the transformation of a continent - Nelson, John William (David J. Weber series in the new borderlands history., 2023)
"John W. Nelson charts the many peoples that traversed and sought power along Chicago's portage paths from the seventeenth to the mid-nineteenth centuries, including Indigenous Illinois traders, French explorers, Jesuit missionaries, Meskwaki warriors, British officers, Anishinaabe headmen, and American settlers. Each group sought to harness Chicago's portages as a space of waterborne movement in a bid for wider regional control. Nelson compellingly demonstrates that even deep within the interior, power relations fluctuated based on the control of waterways and local environmental knowledge. The book challenges readers to take waterborne mobility and strategic geography seriously while showing how Native peoples, along with incoming Europeans, leveraged Chicago's waterways and portage paths to consolidate their control over the region. Pushing beyond political and cultural explanations for Indigenous-European relations and eventual US conquest in the borderlands of North America, Nelson shows how the environments in which collaboration and contest took place directly influenced such interactions"--